Political, economic and environmental concerns: discussion. (28th July 2017) - Skinner, Guy C. G.; Dear, Felicity F.
Abstract : This session concerned the political, economic and environmental impact on the hydrogen economy due to hydrogen embrittlement. This article is part of the themed issue 'The challenges of hydrogen and metals'.